2022
DOI: 10.1108/jaee-12-2020-0331
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management by family firms to meet the debt covenants: evidence from India

Abstract: PurposeGiven the unique nature of Indian family firms and the recent failure of many business houses (Bhushan Steel Ltd., Hotel Leela Ventures Ltd. etc.) it is important to understand the relationship between the earnings management practices of the family firms and the debt. In this paper an attempt towards this has been made.Design/methodology/approachThis study makes use of an empirical approach to understand the relationship between earnings management and debt in the Indian context. This study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…Previous studies have shown that managers incur personal consequences after covenant violations, such as more forced CEO turnover (Ozelge and Saunders, 2012). Many studies have found that companies use accrual earnings management (AEM) and real earnings management (REM) to prevent violating income statement and balance sheet covenants for the same reason (Jha, 2013; Franz et al , 2014; Kim et al , 2017; Ater and Hansen, 2020; Avabruth and Padhi, 2023; Dyreng et al , 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that managers incur personal consequences after covenant violations, such as more forced CEO turnover (Ozelge and Saunders, 2012). Many studies have found that companies use accrual earnings management (AEM) and real earnings management (REM) to prevent violating income statement and balance sheet covenants for the same reason (Jha, 2013; Franz et al , 2014; Kim et al , 2017; Ater and Hansen, 2020; Avabruth and Padhi, 2023; Dyreng et al , 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Due to many factors, credit markets are likely to encourage managers to engage in categorization shifting. Financial goals, such as debt-to-equity ratios or interest coverage ratios, are frequently included in debt covenants (Avabruth and Padhi, 2023). Management may falsify financial statements and accomplish these goals by engaging in classification shifting, which can assist the company in avoiding default and maintaining access to credit markets.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2012). Drawing on the same tenets, several studies found that firms engage in accrual earnings management (AEM) [1] and real earnings management (REM) [2] to avoid the violation of income statement and balance sheet-based covenants (for instance, DeFond and Jiambalvo, 1994; Jaggi and Lee, 2002; Chamberlain et al ., 2014; Franz et al ., 2014; Kim et al ., 2017; Ater and Hansen, 2020; Avabruth and Padhi, 2023; Dyreng et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We examine our research questions under Indian institutional settings because bank debt is the main source of borrowing in India (Allen et al ., 2012), where EBITDA and sales-based covenants are the most commonly used covenants (Avabruth and Padhi, 2023). Based on the sample of Bombay Stock Exchange (BSE)-listed firms spanning over thirteen years from March 2009 to March 2021, we find that firms prefer revenue shifting over expense shifting to avoid the violation of debt covenants.…”
Section: Introductionmentioning
confidence: 99%